THE INFLUENCE OF DIGITAL TECHNOLOGY DEVELOPMENTS ON VOCATIONAL SCHOOL CURRICULUM IN MEETING THE NEEDS OF HUMAN RESOURCES IN THE INDONESIAN EDUCATION - Sabrina, Yuanita; Hamzah, Muhammad Ustman Amrul; Muliyana, Yuni; Fatimah, Asti; Chaerani, Laras (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
The rapid development of digital technology in the era of the Fourth Industrial Revolution (Industry 4.0) and Society 5.0 has brought significant transformation to vocational education, particularly within Indonesian vocational high schools (SMK). This transformation requires a curriculum that is adaptive, integrative, and aligned with the needs of the business sector, industry, and the labor market (DUDIKA). This study aims to analyze how digital technology influences the design, implementation, and effectiveness of the SMK curriculum in preparing competent graduates who meet modern industrial demands. The research employed a Literature Study (LS) method by reviewing 10 scientific articles related to digital technology, curriculum development, teacher competencies, student competencies, and vocational education policies. The findings reveal that the integration of digital technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), and Teacher Digital Competencies (TDC) plays a crucial role in increasing the relevance of vocational learning to current industry needs. These technologies not only enhance instructional methods but also support the development of digital literacy, creativity, problem-solving abilities, and students’ understanding of digitalized industrial processes.